ROLE OF COMPENSATION IN IMPROVING EMPLOYEE WORK PRODUCTIVITY AT PT. INFOMEDIA NUSANTARA, OCC DWS PROJECT DIVISION, SOUTH JAKARTA - Ana Septia Rahman; Dewi Nari Ratih Permada; Riri Oktarini (International Journal Multidisciplinary Science, 2025)
This study analyzes the role of compensation in improving employee productivity at PT. Infomedia Nusantara, OCC DWS Project Division, South Jakarta. Using a qualitative descriptive approach, the study involves interviews, observations, and documentation, focusing on 80 employees. Compensation, both financial and non-financial, is examined for its impact on motivation and productivity. Financial compensation includes salaries, bonuses, and insurance, while non-financial aspects cover recognition and a positive work environment. Findings reveal that compensation significantly influences employee productivity. Financial compensation, such as timely salary payments and performance-based incentives, increases employee motivation and satisfaction, leading to improved task completion and efficiency. However, the suspension of annual leave during the pandemic negatively impacted morale and work-life balance, highlighting the importance of maintaining non-financial compensation for sustained productivity. The SWOT analysis underscores the strengths of robust infrastructure and certified employees but identifies challenges, such as limited training opportunities and reduced benefits. To address these, the study suggests enhancing financial rewards and reintroducing non-financial benefits, such as flexible leave policies. This research concludes that fair and consistent compensation enhances employee performance, benefiting both employees and the organization. PT. Infomedia Nusantara is encouraged to balance financial and non-financial compensation to maintain employee satisfaction and productivity.